2016
DOI: 10.1371/journal.pone.0159745
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of Epileptogenesis-Evoked Upregulation of Matrix Metalloproteinase-9 in Hippocampus

Abstract: Enhanced levels of Matrix Metalloproteinase-9 (MMP-9) have been implicated in the pathogenesis of epilepsy in humans and rodents. Lack of Mmp-9 impoverishes, whereas excess of Mmp-9 facilitates epileptogenesis. Epigenetic mechanisms driving the epileptogenesis-related upregulation of MMP-9 expression are virtually unknown. The aim of this study was to reveal these mechanisms. We analyzed hippocampi extracted from adult and pediatric patients with temporal lobe epilepsy as well as from partially and fully penty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
0
22
0
1
Order By: Relevance
“…The transcriptional regulator Yin Yang 1 (YY1) plays an important role in MMP-9 expression in brain neurons [ 30 , 31 ]. Furthermore, it was reported that HDAC8 inhibition represses the transcriptional activity of YY1 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptional regulator Yin Yang 1 (YY1) plays an important role in MMP-9 expression in brain neurons [ 30 , 31 ]. Furthermore, it was reported that HDAC8 inhibition represses the transcriptional activity of YY1 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several transcription factors have also been described to be involved in MMP-9 expression, including NF-κB, AP-1, SP-1 and Ets [ 29 ]. MMP-9 could also be regulated negatively by transcription factor Yin Yang1 (YY1) in rat non-depolarized brain neurons [ 30 , 31 ]. However, it remains unclear whether HDAC8 inhibition influences the function of transcription factors on MMP-9 and pro-inflammatory cytokine expression in monocytic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MMP-9 is an essential regulator of dendritic spine dynamics (Jasinska et al 2016, Kondratiuk et al 2016, Michaluk et al 2011, Szepesi et al 2013, 2014. In addition to its role in brain physiology, MMP-9 was shown to be implicated in aberrant plasticity and contributes to various brain disorders, such as epilepsy, alcoholism, stress, and schizophrenia (Lepeta et al 2017, Pijet et al 2018, Samochowiec et al 2010, Wilczynski et al 2008, Zybura-Broda et al 2016).…”
Section: Downstream and Upstream C-fosmentioning
confidence: 99%
“…Recently, Pijet et al [117] have employed traumatic brain injury-evoked epileptogenesis, clinically relevant mouse model, to demonstrate important contribution of MMP-9 to epilepsy development. Most interestingly, elevated MMP-9 was found in human epileptic brain samples [118][119][120][121]. Furthermore, Zybura-Broda et al [121] implicated progressive increase in MMP-9 levels, possibly dependent on its gene promoter demethylation, in human epilepsy and rat epileptogenesis.…”
Section: Mmp-9 In Neuropsychiatric Disorders: a Case Of Aberrant Synamentioning
confidence: 97%